A Quick Test of Cognitive Speed: norm-referenced criteria for 121 Italian adults aged 45 to 90 years. (September 2014) - Petrazzuoli, Ferdinando; Palmqvist, Sebastian; Thulesius, Hans; Buono, Nicola; Pirrotta, Enzo; Cuffari, Alfredo; Cambielli, Marco; D'Urso, Maurizio; Farinaro, Carmine; Chiumeo, Francesco; Marsala, Valerio; Wiig, Elisabeth H.
ABSTRACT Background: A Quick Test of Cognitive Speed (AQT) is a brief test that can identify cognitive impairment. AQT has been validated in Arabic, English, Greek, Japanese, Norwegian, Spanish, and Swedish. The aim of this study was to develop Italian criterion-referenced norms for AQT. Methods: AQT consists of three test plates where the patient shall rapidly name (1) the color of 40 blue, red, yellow, or black squares (AQT color), (2) the form of 40 black figures (circles, squares, triangles, or rectangles; AQT form), (3) the color and form of 40 figures (consisting of previous colors and forms; AQT color–form). The AQT test was administered to 121 Italian cognitively healthy primary care patients (age range: 45–90 years). Their mean Mini-Mental State Examination (MMSE) score was 28.8 ± 0.9 points (range 26–30 points). AQT naming times in seconds were used for developing preliminary criterion cut-off times for different age groups. Results: Age was found to have a significant moderate positive correlation with AQT naming times color (r = 0.65, p < 0.001), form (r = 0.53, p < 0.001), color–form (r = 0.63, p < 0.001) and a moderate negative correlation with MMSE score (r = –0.44, p < 0.001) and AQT naming times differed significantly between younger (45–55 years old), older (56–70 years old), and the oldest (71–90 years old) participants. Years of education correlated positively but weakly with MMSE score (r = 0.27, p = 0.003) and negatively but weakly with AQT color (r = –0.16, p = ns), form (r = –0.24, p = 0.007), and color–form (r = –0.19, p = 0.005). We established preliminary cut-off times for the AQT test based on +1 and +2 standard deviations according to the approach in other languages and settings. Conclusions: This is the first Italian normative AQT study. Future studies of AQT – a test useful for dementia screening in primary care – will eventually refine cut-off times for normality balancing sensitivity and specificity in cognitive diagnostics.